RETURN ON ASSETS, DEBT TO EQUITY RATIO, TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN - Febrica , Jesisca; Lekok, Widyawati (E-Jurnal Akuntansi TSM, 2023)
The purpose of this study is to provide empirical evidence about the factors that affect firm value in Indonesia. Those factors are return on assets, debt to equity ratio, current ratio, dividend payout ratio, tax avoidance, and firm size. This study uses a population of non-finance companies that are listed in Indonesia Stock Exchange in the year 2019-2021. The selection sample in this study research was based on purposive sampling technique with a total 237 data samples used. This study uses a multiple regression model. The results of this study indicate that the return on assets has a positive effect on firm value, the greater return on assets can indicate that management is doing a good job thereby increasing firm value. The results of the debt to equity ratio have a positive effect on firm value, a high debt to equity ratio reflects that the company has a long-term investment strategy so that investors will invest in the company so that it will increase the firm value. The results of tax avoidance have a positive effect on firm value, tax avoidance can indicate a manager's personal motivation to manipulate company profits and provide false information to investors so that less tax avoidance can increase firm value. Meanwhile, the current ratio, dividend payout ratio, and firm size have no effect on firm value.